Tuberculosis with cavities? Rapid diagnosis of Rhodococcus equi pulmonary infection with cavities by acid-fast staining: A case report - Jiang, Yuhang; Li, Jian; Qin, Weichao; Gao, Yuan; Liao, Xin; Zeng, Yan (Frontiers in Public Health, 2022)
Rhodococcus equi is a kind of conditionally pathogenic bacteria that is widely distributed in soil, water and marine environments and can cause respiratory infections, pleurisy, bloodstream and even bone marrow infections in immunocompromised people, especially the AIDS patients. This case reported that a patient initially suspected that he had tuberculosis and was seen in the tuberculosis clinic. However, we found the Rhodococcus equi from his outpatient sputum through the acid-fast stain, and whose acid-fast stain could be positive. Then we suggested to the doctor that the patient might have pulmonary infection with Rhodococcus equi. The patient was subsequently admitted to the respiratory unit for treatment, after the source of the infection was identified, the patient was treated with a combination of antibiotics for a fortnight and discharged with significantly improved symptoms.